PENGARUH FINANCIAL TECHNOLOGY (FINTECH) TERHADAP STABILITAS SISTEM KEUANGAN DI INDONESIA - Saraswati, Birgitta Dian; Tisnawati, Ni Made (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.10.NO.10.TAHUN.2021, 2021)
Financial stability is very important in the economy because financial stability will ensure smooth financial transactions in the economy.This study aims to analyze the effect of P2P lending fintech, payment fintech and macroeconomic variables (inflation, interest rates and exchange rates) on financial stability in Indonesia.This study uses time series data with the period 2018.1-2021.4. Using the Vector Error Correction Model, this research shows that Fintech P2P Lending, Fintech Payments and macroeconomic variables (inflation, interest rates and exchange rates) affect the financial stability in Indonesia only in the long term.Fintech P2P lending in the long term will lead to financial system instability, while Fintech payments in the long term have a positive effect on financial system stability in Indonesia. This has policy implications where through the role of the Financial Services Authority it is necessary to regulate and supervise P2P lending fintech. In addition, considering that payment fintech has a positive impact on financial system stability in Indonesia, through the role of Bank Indonesia, it is necessary to design policies to increase the use of non-cash payment instruments.